The Role of School-Based Psychological Support in Reducing Symptoms of PTSD in Bullying Victims in Thai Middle Schools - Nattapong S. Srisai (Journal of Advanced Research in Education, 2025)
This paper explores the role of school-based psychological support in alleviating symptoms of Post-Traumatic Stress Disorder (PTSD) in bullying victims in Thai middle schools. Bullying remains a significant issue in Thai educational settings, with various forms of bullying—physical, verbal, social, and cyberbullying—impacting students’ mental health. These traumatic experiences can lead to PTSD, characterized by symptoms such as anxiety, avoidance, and hyperarousal. School-based psychological interventions, including individual counseling, group therapy, cognitive behavioral therapy (CBT), and trauma-informed care, are increasingly integrated into Thai schools to address these psychological needs. However, challenges such as the lack of trained professionals, cultural stigma, reluctance to seek help, and logistical barriers hinder the effectiveness of these programs. This paper highlights the importance of improving access to psychological support, providing adequate resources, and overcoming cultural barriers to mental health care in schools to ensure that bullying victims receive the help they need.